NATURAL AND ENVIRONMENTAL VULNERABILITY OF THE JAURU RIVER BASIN-MATO GROSSO, BRAZIL - da Silva Luz, Camila Calazans; Ramos, Alexander Webber Perlandim; Silva, Gessica de Jesus Oliveira (Ra'e Ga: o Espaço Geográfico em Análise, 2019)
The disorderly use of land is currently one of the main causes of environmental problems. From this perspective, the objective of this study was to determine the natural and environmental vulnerability of the Jauru river basin in the Brazilian state of Mato Grosso. This goal was made from the perspective that the results generated contribute to environmental planning and management, considering that the Jauru river is tributary of the Paraguay river, responsible for the flooding of the Pantanal plain and, that possible impacts caused by the basin may compromise the dynamic equilibrium of the Pantanal's flood pulse. The model of assessment of natural and environmental vulnerability was adopted, with the identification of the following environmental characteristics: geology, slope, agricultural aptitude and vegetation cover and land use. Data were related through Geographic Information Systems to generate natural and environmental vulnerability maps. It was verified, through the data obtained, that in both vulnerabilities studied there was a predominance of the middle class, mainly resulting from the presence of fragile soils. Also, the predominance of the classes of agricultural aptitude found in the basin, as well as the suppression of the natural vegetation to expand the pasture areas. It was concluded that the areas covered by natural vegetation and/or pastures, in the Jauru river basin, present average natural vulnerability and state of medium to high environmental vulnerability, evidencing that livestock, the main activity regional economic development, has been developed in disagreement with environmental aptitude, contributing to the elevation of the state of environmental vulnerability in the basin.